2018
DOI: 10.1002/jssc.201700833
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of total cholesterol in human milk by gas chromatography

Abstract: Human milk provides the key nutrients necessary for infant growth and development. The objective of this study was to develop and validate a method to analyze the cholesterol content in liquid human milk samples along lactation. Direct saponification of the sample using ethanolic potassium hydroxide solution under cold conditions was applied and unsaponifiable matter was separated by centrifugation. Cholesterol was converted into its trimethylsilyl ether and the derivative analyzed by gas chromatography couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
1
8
0
3
Order By: Relevance
“…[31,32] Our data indicated that the levels of cholesterol decreased from colostrum (15.2-22.6 mg per 100 g milk) to mature milk (13.8-16.6 mg per 100 g milk), in agreement with studies in other countries. [7,8,33,34] Infants need enough cholesterol in the early stages to help their nervous system development, and because the cholesterol synthesis in the baby was not enough, it must be obtained from the diet. These may be caused by higher contents of cholesterol in colostrum than in mature milk.…”
Section: Cholesterol In Hm and Infant Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…[31,32] Our data indicated that the levels of cholesterol decreased from colostrum (15.2-22.6 mg per 100 g milk) to mature milk (13.8-16.6 mg per 100 g milk), in agreement with studies in other countries. [7,8,33,34] Infants need enough cholesterol in the early stages to help their nervous system development, and because the cholesterol synthesis in the baby was not enough, it must be obtained from the diet. These may be caused by higher contents of cholesterol in colostrum than in mature milk.…”
Section: Cholesterol In Hm and Infant Formulasmentioning
confidence: 99%
“…Research showed that the contents of cholesterol were not affected by maternal diet, but the levels of cholesterol were correlated with lactation period. Maurizio Beggio et al . reported the levels of cholesterol in HM of Singapore decreased from 13.1 mg per 100 g (1 month) to 11.3 mg per 100 g (4 months) after delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados mostraram que as concentrações dos ácidos oleico, palmitoleico e linoleico aumentaram nas amostras coletadas na quarta semana, quando comparados com aquelas coletadas nos primeiros sete dias após o parto. 22 Apesar da GC ser amplamente utilizada para determinação de AGs, Beggio et al (2018) desenvolveram e validaram um método para quantificar o teor de colesterol em amostras de LH com o uso da GC-FID. Eles observaram que o teor de colesterol, durante as fases de lactação, diminuiu ligeiramente ao longo do tempo de 13,1 mg/100 g no 1° mês para 11,3 mg/100 g 120 dias após o parto.…”
Section: Cromatogra Ia Em Fase Gasosa (Gc)unclassified
“…Eles observaram que o teor de colesterol, durante as fases de lactação, diminuiu ligeiramente ao longo do tempo de 13,1 mg/100 g no 1° mês para 11,3 mg/100 g 120 dias após o parto. 61 3.5.1. Derivatização lipídica para a análise da composição em ácidos graxos Após a extração dos lipídios das amostras de LH, a composição em AGs é comumente determinada por GC, empregando-se como preparo de amostra a hidrólise dos TAGs seguida de derivatização (transformação lipídica) dos AGs livres resultantes, formando-se uma mistura de EMAGs ou de ésteres etílicos de ácidos graxos (EEAGs ou FAEEs -fatty acid ethyl esters), quando metanol e etanol são utilizados, respectivamente.…”
Section: Cromatogra Ia Em Fase Gasosa (Gc)unclassified
See 1 more Smart Citation